Histology of the hepatopancreas and anterior intestine in the freshwater prawn Macrobrachium carcinus (Crustacea, Decapoda) - Rocha Ruiz, Thalles Fernando [UNESP]; Vidal, Mateus Rossetto [UNESP]; Ribeiro, Karina; Vicentini, Carlos Alberto [UNESP]; Franceschini Vicentini, Irene Bastos [UNESP] (Soc Brasileira Carcinologia, 2020)
The purpose of this study was to describe the structure of the midgut (hepatopancreas and intestine) in the endemic species, Macrobrachium carcinus. Thirty specimens were collected, and the midgut was fixed in Bouin's solution for histological and histochemical analyzes by light microscopy. The hepatopancreas consists of two lobes that connect to the end of the stomach by primary ducts, which originate secondary tubules or hepatopancreatic ducts, that branch into hepatopancreatic tubules. The hepatopancreatic duct presents a columnar epithelium composed of R- and F- cells with evident brush borders for absorption and storage. The hepatopancreatic tubule is lined by epithelium with five cell types (E, F, R, B, and M). The distal region presents all cell types, with a predominance of E-cells that correspond to epithelial renewal. The middle region presents F- and B- cells, characteristic of extracellular and intracellular digestion. The proximal region, with B- and R- cells, performs the final digestion, storage, and extrusion of the cells with waste material. The intestine is lined by a single cell type with an evident brush border, suggesting luminal absorption. This cellular arrangement along the length of the midgut proposes distinct morpho-functional characteristics of digestion, absorption, and storage in this species.
Keywords: Hepatopancreas; intestine; epithelium; cytoarchitecture; brush border